2011
DOI: 10.1111/j.1742-4658.2011.08401.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a hypertriglyceridemic transgenic miniature pig model expressing human apolipoprotein CIII

Abstract: Hypertriglyceridemia has recently been considered to be an independent risk factor for coronary heart disease, in which apolipoprotein (Apo)CIII is one of the major contributory factors, as it is strongly correlated with plasma triglyceride levels. Although ApoCIII transgenic mice have been generated as an animal model for the study of hypertriglyceridemia, the features of lipoprotein metabolism in mice differ greatly from those in humans. Because of the great similarity between pigs and humans with respect to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 28 publications
4
37
0
1
Order By: Relevance
“…In contrast, a premature stop mutation in apolipoprotein C-III (apoC-III) is associated with low levels of plasma triglycerides (5). This finding in humans is in line with studies demonstrating that apoC-III knock-out mice are hypotriglyceridemic (6), whereas overexpression of apoC-III in mice leads to hypertriglyceridemia (7)(8)(9). ApoC-III is known to inhibit LPL activity in vitro (10 -12).…”
supporting
confidence: 63%
See 1 more Smart Citation
“…In contrast, a premature stop mutation in apolipoprotein C-III (apoC-III) is associated with low levels of plasma triglycerides (5). This finding in humans is in line with studies demonstrating that apoC-III knock-out mice are hypotriglyceridemic (6), whereas overexpression of apoC-III in mice leads to hypertriglyceridemia (7)(8)(9). ApoC-III is known to inhibit LPL activity in vitro (10 -12).…”
supporting
confidence: 63%
“…It is not yet known where angptl4 acts on LPL in vivo, whether this occurs on the endothelium in contact with blood, or whether angptl4 acts on LPL along its transport route to the luminal side of the endothelium. Transgenic miniature pigs that overexpress human apoC-III have similar levels of LPL activity that can be released to blood by heparin when compared with their wild-type littermates, indicating that the luminal LPL activity is not affected (8). Effects on in the heparin-releasable LPL activity of one tissue could, however, be masked by release of LPL from other tissues as seen in heart-specific overexpression of angptl4 (65) and in mice defi-cient in LPL in adipose tissue (66).…”
Section: Discussionmentioning
confidence: 99%
“…The overall pregnancy rate for HMC has increased from about 55 % to over 80 % according to the latest figure reported by two laboratories (in Denmark and China, respectively) that use HMC for large scale pig cloning (Schmidt et al 2010). However, further improvements are still required as high frequencies of prenatal and postnatal death of the cloned pigs are observed by us and others (Rogers et al 2008a;Luo et al 2011c;Wei et al 2012. Insufficient reprogramming of the somatic cell genome is suggested to be the major cause of these abnormalities, as aberrant DNA methylation was found in the cloned pigs with abnormal phenotypes (Kang et al 2001;Xue et al 2002). However, we also found that phenotypically normal cloned pigs are highly similar to non-cloned pigs in their genome-wide DNA methylation levels (Gao et al 2011a;Gao et al 2011b).…”
Section: (Weiss Et Al 2009)supporting
confidence: 65%
“…Two GM pigs, expressing hTPO (Cho et al 2007) or hApoCIII (Wei et al 2012), have been generated in order to study platelet disorder and hypertriglyceridemia, respectively.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…Experimental models of hyperlipidemia to date include highfat dietor fructoseenriched diet-fed mice or rats (4,5), apolipo protein E-deficient (ApoE−/−) mice (6), LDL receptordeficient (Ldlr −/−) hypercholesterolaemic mice (7), glutamatecysteine ligase modifier subunit genedeficient [Gclm(−/−) mice (8), APOE*3Leiden.cholesteryl ester transfer protein (E3L.CETP)] (9), or ApoCIII transgenic mice or pigs (10) as well as combination of Ldlr −/− and high-fat diet-fed mice (7). Interestingly, ApoCIII trans genic animals showed significantly increased plasma triglyceride (TG) levels, but with minimal changes in plasma cholesterol (TC) concentrations (11).…”
Section: Introductionmentioning
confidence: 99%